The Epistemic Imperialism of Science. Reinvigorating Early Critiques of Scientism - Mazur, Lucas B. (Frontiers in Psychology, 2021)
Positivism has had a tremendous impact on the development of the social sciences over the past two centuries. It has deeply influenced method and theory, and has seeped deeply into our broader understandings of the nature of the social sciences. Postmodernism has attempted to loosen the overly rigid grip of positivism on our thinking, and while it has not been without its successes, postmodernism has worked more to deconstruct positivism than to construct something new in its place. Psychologists today perennially wrestle to find and retain their intellectual balance within the methodological, theoretical, and epistemological struggles between positivism and postmodernism. In the process, pre-postmodern criticisms of positivism have been largely forgotten. Although they remain deeply buried at the core of psychology, these early alternatives to positivism are rarely given explicit hearing today. The current piece explores some of the early critiques of positivism, particularly of its scientism, as well as early suggestions to tip the scales (back) in favor of sapientia (“wisdom”). This third option, largely overlooked within mainstream psychology, is of tremendous value today as it is both deconstructive and constructive relative to the shortcomings of positivism. It avoids the overly reductionistic “trivial order” of positivism, as well as the deeply unsatisfying and disorienting “barbaric vagueness” of postmodernism, while simultaneously embracing important core elements of both currents of thought.